Gate‐Induced Massive and Reversible Phase Transition of VO2 Channels Using Solid‐State Proton Electrolytes. (13th July 2018) - Jo, Minguk; Lee, Hyeon Jun; Oh, Chadol; Yoon, Hyojin; Jo, Ji Young; Son, Junwoo
Abstract: The use of gate bias to control electronic phases in VO2, an archetypical correlated oxide, offers a powerful method to probe their underlying physics, as well as for the potential to develop novel electronic devices. Up to date, purely electrostatic gating in 3‐terminal devices with correlated channel shows the limited electrostatic gating efficiency due to insufficiently induced carrier density and short electrostatic screening length. Here massive and reversible conductance modulation is shown in a VO2 channel by applying gate bias V G at low voltage by a solid‐state proton (H + ) conductor. By using porous silica to modulate H + concentration in VO2, gate‐induced reversible insulator‐to‐metal (I‐to‐M) phase transition at low voltage, and unprecedented two‐step insulator‐to‐metal‐to‐insulator (I‐to‐M‐to‐I) phase transition at high voltage are shown. V G strongly and efficiently injects H + into the VO2 channel without creating oxygen deficiencies; this H + ‐induced electronic phase transition occurs by giant modulation (≈7%) of out‐of‐plane lattice parameters as a result of H + ‐induced chemical expansion. The results clarify the role of H + on the electronic state of the correlated phases, and demonstrate the potentials for electronic devices that use ionic/electronic coupling. Abstract : Gate‐induced massive and reversible phase transition is demonstrated in VO2 channels using solid‐state proton electrolytes. Applying gate bias effectively injects large numbers of H + ions without creating oxygen deficiencies and causes a two‐step insulator‐to‐metal‐to‐insulator phase transition and a hydrogen‐defect‐induced chemical expansion at room temperature. This observation presents an opportunity to develop new types of three‐terminal electronic devices.